2008
DOI: 10.3324/haematol.13156
|View full text |Cite
|
Sign up to set email alerts
|

Anemia and survival in childhood acute lymphoblastic leukemia

Abstract: BackgroundSeveral studies have demonstrated that patients with childhood acute lymphoblastic leukemia presenting with mild anemia at diagnosis have an increased risk of poor outcome compared to patients with more severe anemia. However, it has not been reported whether there is any correlation between degree of anemia and leukemia subtype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 38 publications
3
19
0
Order By: Relevance
“…30 Teuffel et al, found a very low hemoglobin levels at diagnosis are associated with more advanced disease in these subgroups, this may be related to the late diagnosis. 31 Initial WBC count is one of the important prognostic factors in ALL and the count above 50.0×109cells/L was considered unfavorable criteria and classified as high risk of relapse, more than 70% of enrolled patients had a count below 50×109cells/L and 29% patients were having WBC count >50.0×109cells/L which was also observed by other study. 10,11 Patients with severe leukocytosis at diagnosis may present bulky tumor mass, mediastinal enlargement, hepatosplenomegaly and significant lymphadenopathy, this finding is usually associated with the unfavorable chromosomal translocations t (4;11) and t (9;22), this association was not proved in the current study and this may be due to small sample size.…”
Section: Discussionsupporting
confidence: 64%
“…30 Teuffel et al, found a very low hemoglobin levels at diagnosis are associated with more advanced disease in these subgroups, this may be related to the late diagnosis. 31 Initial WBC count is one of the important prognostic factors in ALL and the count above 50.0×109cells/L was considered unfavorable criteria and classified as high risk of relapse, more than 70% of enrolled patients had a count below 50×109cells/L and 29% patients were having WBC count >50.0×109cells/L which was also observed by other study. 10,11 Patients with severe leukocytosis at diagnosis may present bulky tumor mass, mediastinal enlargement, hepatosplenomegaly and significant lymphadenopathy, this finding is usually associated with the unfavorable chromosomal translocations t (4;11) and t (9;22), this association was not proved in the current study and this may be due to small sample size.…”
Section: Discussionsupporting
confidence: 64%
“…1 a , left). As cell lines grown in culture may have acquired additional mutations and epigenetically induced changes in gene expression, we further compared the list of 32 genes to data derived from patient samples of Ewing's sarcoma, neuroblastoma, rhabdomyosarcoma and acute lymphoblastic leukemia (ALL29–31; see Material and Methods). Three hundred and thirteen probesets were identified to be differentially expressed in Ewing's patients with a p ‐value of <0.001 and a fold change of >3.5 compared to the other tumor types (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Multidrug chemotherapy allows effective treatment of more than 70% of children with neoplasms, independently of the disease type or stage [19]. Unfortunately, chemotherapeutics are not selective and have a low therapeutic index, which results in damaging also healthy cells.…”
Section: Introductionmentioning
confidence: 99%